A comprehensive review on disposition kinetics and dosage of oral administration of Andrographis paniculata, an alternative herbal medicine, in co-treatment of coronavirus disease - Songvut, Phanit; Suriyo, Tawit; Panomvana, Duangchit; Rangkadilok, Nuchanart; Satayavivad, Jutamaad (Frontiers in Pharmacology, 2022)
Coronavirus disease 2019 (COVID-19) is a current global health crisis that is driving the investigation of alternative phytomedicines for antiviral purposes. The evidence suggests that Andrographis paniculata crude or extract is a promising candidate for treating symptoms of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This review, aims to consolidate the available reports on the disposition kinetics of andrographolide, a main active component of A. paniculata. The second objective of this review is to summarize the available reports on an appropriate oral dosage for the use of andrographolide in upper respiratory tract infections (URTIs) and in other viral infectious diseases. The data were collected from the literature on absorption, distribution, biotransformation and excretion of andrographolide, and information was also obtained from scientific databases about the use of A. paniculata. The finding of this review on pharmacokinetics indicates that andrographolide is slightly absorbed into the blood circulation and exhibits poor oral bioavailability, whereas its distribution process is unrestricted. In the termination phase, andrographolide preferentially undergoes biotransformation partly through a phase I hydroxylation and phase II conjugation, it is then eliminated via the renal excretion and hepatobiliary system. The key summary on recommended dosage for andrographolide in uncomplicated URTI treatment is 30 mg/day for children and 60 mg/day for adults. The dose for adult patients with pharyngotonsillitis could be increased to 180 mg/day, but not exceed 360 mg/day. Co-treatment with A. paniculata in concert with the standard supportive care for influenza reduced the severity of symptoms, shortened treatment duration, and decreased the risk of developing post-influenza complications. The recommended starting dose for use in patients with mild COVID-19 is 180 mg/day of andrographolide, based on the dose used in patients experiencing a URTI with inflammation. This review is not only applicable for evaluating the appropriate doses of andrographolide for antiviral treatments, but also encourages future research evaluating the effectiveness of these recommended dosages during the COVID-19 pandemic.